Admissibility of the Use of Electronic Means of Evidence Obtained Unlawfully in a Civil Proceeding - Klich, Aleksandra (Teisė, 2019)
The admissibility of the use of evidence obtained unlawfully, referred to as the fruit of the poisonous tree, still remains an unresolved issue on the basis of Polish procedural law. The author in her paper will focus on such forms of evidence, which are more and more often the subject of evidentiary procedures, noting that this mainly concerns the content of private conversations conducted with the use of messengers and community portals, call recordings, and telephone billings, data obtained from mobile phones, or so-called print screens, which are often obtained in an illegal manner, interfering with the sphere of privacy of the other person.
Keywords: civil proceeding; electronic evidence; illegal evidence; evidence obtained unlawfully